2019
DOI: 10.1016/j.isci.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes Latently Infected with Human Cytomegalovirus Evade Neutrophil Killing

Abstract: SummaryOne site of latency of human cytomegalovirus (HCMV) in vivo is in undifferentiated cells of the myeloid lineage. Although latently infected cells are known to evade host T cell responses by suppression of T cell effector functions, it is not known if they must also evade surveillance by other host immune cells. Here we show that cells latently infected with HCMV can, indeed, be killed by host neutrophils but only in a serum-dependent manner. Specifically, antibodies to the viral latency-associated US28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 83 publications
1
38
0
Order By: Relevance
“…We next assessed whether downregulation of IFI16 and MNDA occurs during long term maintenance of latency; long term downregulation of HLA-DR is already known to be important for latent carriage of HCMV 41 . We infected monocytes with HCMV that drives mCherry from GATA2 promoter, and maintains this marker for far longer during latency than SV40 promoter-driven tags 51 . At 10 and 14 d.p.i., IFI16 remained absent and MNDA remained partially downregulated in infected cells (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next assessed whether downregulation of IFI16 and MNDA occurs during long term maintenance of latency; long term downregulation of HLA-DR is already known to be important for latent carriage of HCMV 41 . We infected monocytes with HCMV that drives mCherry from GATA2 promoter, and maintains this marker for far longer during latency than SV40 promoter-driven tags 51 . At 10 and 14 d.p.i., IFI16 remained absent and MNDA remained partially downregulated in infected cells (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…TB40/E BAC4 IE2-eYFP has been described previously 49,50 . TB40/E BAC4 GATA2mCherry has been described previously 51 . TB40/E with deleted NF-κB sites in the MIEP at positions −94, −157, −262 and −413, and the revertant virus, were a kind gift from Jeffery Meier and Ming Li (University of Iowa, United States), and have been described previously 52 .…”
Section: Methodsmentioning
confidence: 99%
“…Expression of US28 in infected HPCs reprograms the cells into immunosuppressive monocytes (Zhu et al, 2018). The reported effects of HCMV infection on monocytes include increased lifespan through induction of anti-apoptotic genes (Chan et al, 2010;Reeves et al, 2012;Collins-McMillen et al, 2015;Peppenelli et al, 2016), re-programming the cells to an M1 or M2-like macrophage phenotype (Smith et al, 2004;Chan et al, 2008Chan et al, , 2012Avdic et al, 2013;Stevenson et al, 2014), modulation of cell signaling pathways (Kew et al, 2017;Krishna et al, 2017) evasion of killing by neutrophils (Elder et al, 2019), and induction of an anergic-like state (Shnayder et al, 2020).…”
Section: Cellular Tropism and Viral Gene Expressionmentioning
confidence: 99%
“…144 In vitro experiments have also shown that human neutrophils do not kill latently HCMV-infected monocytes owing to a suppressed secretion of neutrophil chemoattractants (i.e., S100A8/A9) by infected monocytes themeselves. 145 However, in contrast to the supportive role of neutrophils toward CMV, an in vivo study conducted in a mouse model of primary MCMV infection reported instead that neutrophils exert TNF-related apoptosis-inducing ligand (TRAIL)-mediated anti-MCMV activity in infected tissues upon their CXCL-1-mediated recruitment. 146 Despite the accumulating findings regarding potential interactions between neutrophils and CMV, both in human and in mouse models, much remains to be defined and clarified.…”
Section: Cytomegalovirus (Cmv) Reactivationmentioning
confidence: 99%